Performance of new issues: The Malaysian case - Saiful Bahri Sufar (Penerbit Universiti Kebangsaan Malaysia, 1989)
This paper examines the performance of new issues in Malaysia. Two aspects of performance were examined. Firstly whether there are any underpricing n Ihe prlcmg of new issues and secondly whether the market is efficient in pricing these shares. The result of this study showed an existence of underpricing as hIgh as 400% and as low as 13%. However, the MalaysIan stock arket is efficient in the pricing of these new Issues. Price of these shares do nol expenence sinificant differences from the initial pircing in the opening wllhm one year after listmg.